Quick-MESS: A fast statistical tool for Exoplanet Imaging Surveys. Issue Volume 8:Issue S299(2013) (6th January 2014) - Bonavita, Mariangela; De Mooij, Ernst; Jayawardhana, Ray; Gratton, Raffaele
Abstract: Several tools have been developed for the analysis of the results of direct imaging exoplanet surveys, mostly using a combination of Monte-Carlo simulations or a Bayesian approach. Here we present a novel approach to the statistical analysis of Direct Imaging surveys, called Quick-MESS, which allows for a much faster and flexible analysis.